Behaviour of density functional theory for electric response properties at distorted geometries of molecules - Shedge, Sapana V.; Joshi, Sayali P.; Pal, Sourav (Theoretical Chemistry Accounts, 2012)
The role of exchange-correlation is well known for accurate calculations of electric response properties. The exchange-correlation functional in density functional theory (DFT) has been well studied for ground state equilibrium geometry. However, the behaviour of these functional in stretched geometries, where static correlation play an important role, has not been studied systematically, particularly for response electric properties. Thus, we present here the rigorous calculation of electric response properties at distorted geometries of the molecules. We have considered dipole polarizability and dipole-quadrupole polarizability for description of role of static and dynamic correlation for electric response properties. The calculations are performed with our new approach, noniterative approximation to coupled-perturbed Kohn-Sham method. These DFT results are compared with higher level ab initio such as coupled perturbed singles and doubles and fully correlated full CI. We have studied single, double and triple-bonded systems at different inter-nuclear separation. We report here the dipole polarizability and dipole-quadrupole polarizability of HF, BH, H2CO, CO and NO+. We also present the effect of basis and functional on polarizability and dipole-quadrupole polarizability.
Keywords: DFT; Dipole-dipole polarizability; Dipole-quadrupole polarizability; Distorted geometry; NIA-CPKS